Wind Turbine Composite Blades: A Critical Review of Aeroelastic Modeling and Vibration Control - Liu, Tingrui; Xu, Dan; Cui, Qinghu (Fluid dynamics & materials processing, 2025)
With the gradual increase in the size and flexibility of composite blades in large wind turbines, problems related to aeroelastic instability and blade vibration are becoming increasingly more important. Given their impact on the lifespan of wind turbines, these subjects have become important topics in turbine blade design. In this article, first aspects related to the aeroelastic (structural and aerodynamic) modeling of large wind turbine blades are summarized. Then, two main methods for blade vibration control are outlined (passive control and active control), including the case of composite blades. Some improvement schemes are proposed accordingly, with a special focus on the industry’s outstanding suppression scheme for stall-induced nonlinear flutter and a new high-frequency micro-vibration control scheme. Finally, future research directions are indicated based on existing research.